PERAN KUA KECAMATAN PAKONG DALAM PENANGANAN DISPENSASI NIKAH PASCA PERUBAHAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN - Siti Zulfatul Mahmudah; Ainol Yaqin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of the Pakong District Office of Religious Affairs (KUA) in handling marriage dispensation cases after the amendment of Law Number 16 of 2019 concerning Marriage, which sets the minimum marriage age at 19 years for both men and women. This research employed a qualitative approach using interviews, observations, and documentation methods. The findings indicate that the Pakong District KUA plays a role in providing education, marriage guidance, and administrative services related to marriage dispensation applications. However, its implementation still faces several challenges, including low public legal awareness, cultural factors, and socio-economic conditions that contribute to the high number of marriage dispensation requests. Therefore, cooperation between the KUA, families, and the community is needed to reduce the rate of early marriage.